PREPARATION OF A YOUNG TEACHER TO INNOVATIVE ACTIVITY BY MEANS COLLECTIVE CREATIVE AFFAIRS - I.A. Voloshchuk (Academy of Cognitive and Natural Sciences, 2022)
In the article the author exposes conditions of the teacher beginner preparation for innovative activity through the organization of collective creative works in the action comities and problem laboratories.